Oxymatrine alleviates Echinococcus multilocularis infection by remodeling the liver immune microenvironment and intestinal flora homeostasis - Zhu, Yazhou; Wu, Peijiao; Wen, Rou; Tang, Jing; Hou, Siyu; Yuan, Shiqin; Li, Zihua; Li, Ming; Zhao, Wei (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundAlveolar echinococcosis (AE) is a zoonotic parasitic disease that poses a grave threat to human health. Recent studies have indicated that the gut microbiota plays a significant role in the pathogenesis of alveolar echinococcosis. Consequently, the quest for innovative microbial targeted modulators is anticipated to address the treatment of alveolar echinococcosis. Oxymatrine, an alkaloid extracted from the legume plant Sophora flavescens, has been demonstrated in research studies to regulate gut microbiota, thus treating various diseases, including rheumatoid arthritis and autoimmune encephalomyelitis. Nevertheless, the role of the aforementioned organism in alveolar echinococcosis remains to be elucidated.MethodsThis study evaluated the effects of oxymatrine (OMT) at concentrations of 0.25 mM, 0.35 mM, 0.75 mM, 1 mM, and 1.25 mM on Echinococcus multilocularis protoscoleces in vitro over 48 hours, with cell viability assessed using the CCK-8 assay. Subsequently, an E. multilocularis infection model was established by intraperitoneal injection in mice. After three months of infection, the mice were treated daily with intraperitoneal injections of OMT at doses of 25 mg/kg, 50 mg/kg, or 100 mg/kg, alongside albendazole as a reference treatment, for two months. Fecal samples from each group were collected for 16S rRNA sequencing. Following treatment, tissue samples were analyzed. The liver and spleen indices were calculated by measuring mouse body weight, cyst weight, liver weight, and spleen weight. Hepatic pathological changes were examined using hematoxylin-eosin (H&E) and Masson’s trichrome staining. Additionally, flow cytometry was performed to quantify changes in hepatic CD4+ T cells, CD8+ T cells, and B cells.ResultsIn vitro experimental results demonstrated that treatment with oxymatrine at concentrations of 0.35 mM, 0.5 mM, 0.75 mM, 1.0 mM, and 1.25 mM significantly reduced the viability of Echinococcus multilocularis protoscoleces compared to the control group. The in vivo experimental results demonstrated that, compared with the control group, the 25 mg/kg, 50 mg/kg, and 100 mg/kg OMT-treated groups exhibited significantly reduced cyst weights, marked alleviation of liver inflammatory cell infiltration and fibrosis, and a significant increase in the number of hepatic CD8+ T cells. Furthermore, the 16S rRNA sequencing analysis revealed that OMT intervention enhanced the diversity of gut microbiota.ConclusionOur data indicate that matrine can directly inhibit the growth of Echinococcus multilocularis in vitro, suggesting that matrine may play a therapeutic role in the early stage of alveolar echinococcosis. In vivo studies have shown that three months after infection, matrine can exert an anti-infection effect in the middle and late stages of alveolar echinococcosis by increasing the diversity of intestinal microbiota and the number of CD8+ T cells.